Symbiotic cognition as an alternative for socially extended cognition. (17th November 2019) - Slors, Marc
ABSTRACT: According to a promising proposal, cognitive abilities and processes in the context of social institutions should be characterized as socially extended cognition. However, this idea invokes resistance because it seems to invoke metaphysical problems such as a serious variant of the problem of cognitive bloat. In this paper, I argue that defenders of socially extended cognition are not overly worried by such problems because their position is akin to a position known as 'distributed cognition, ' which avoids these problems. Nevertheless, I will argue that the explanatory aims of socially extended cognition do not correspond to the distributed cognition perspective. The ensuing predicament can be avoided, however, by recognizing that the idea of socially extended cognition hinges on the conflation of two dimensions of the interconnection of the elements in a cognitive system, which I will label 'functional integration' and 'task-dependency.' Separating these dimensions allows us to identify an overlooked alternative for extended and distributed cognition – symbiotic cognition – that fits cognition in social institutions better than both and avoids the predicament.